Assessing the physiological relevance of alternate architectures of the p7 protein of hepatitis C virus in different environments. Issue 20 (15th October 2016) - Holzmann, Nicole; Chipot, Christophe; Penin, François; Dehez, François
Graphical abstract: Abstract: The viroporin p7 of the hepatitis C virus forms multimeric channels eligible for ion transport across the endoplasmic reticulum membrane. Currently the subject of many studies and discussion, the molecular assembly of the ion channel and the structural characteristics of the p7 monomer are not yet fully understood. Structural investigation of p7 has been carried out only in detergent environments, making the interpretation of the experimental results somewhat questionable. Here, we analyze by means of molecular dynamics simulations the structure of the p7 monomer as a function of its sequence, initial conformation and environment. We investigate the conductance properties of three models of a hexameric p7 ion channel by examining ion translocation in a pure lipid bilayer. It is noteworthy that although none of the models reflects the experimentally observed trend to conduct preferentially cations, we were able to identify the position and orientation of titratable acidic or basic residues playing a crucial role in ion selectivity and in the overall conductance of the channel. In addition, too compact a packing of the monomers leads to channel collapse rather than formation of a reasonable pore, amenable to ion translocation. The present findings are envisioned to help assess the physiological relevance of p7 ion channel models consisting of multimeric structures obtained in non-native environments.